2022
DOI: 10.1096/fj.202100822rr
|View full text |Cite
|
Sign up to set email alerts
|

CD44 mediates shear stress mechanotransduction in an in vitro blood‐brain barrier model through small GTPases RhoA and Rac1

Abstract: Fluid shear stress is an important mediator of vascular permeability, yet the molecular mechanisms underlying the effect of shear on the blood‐brain barrier (BBB) have yet to be clarified in cerebral vasculature despite its importance for brain homeostasis. The goal of this study is to probe components of shear mechanotransduction within the BBB to gain a better understanding of pathologies associated with changes in cerebral perfusion including ischemic stroke. Interrogating the effects of shear stress in viv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 56 publications
4
20
0
Order By: Relevance
“…RhoA inhibition was already reported in bovine primary BMEC cultured one day at 10 dyn.cm −2 [ 80 ]. More recently, DeOro et al reported in a pre-print an inhibition of RhoA in hCMEC/D3 cells (4 days at 2.1 dyn.cm −2 ) [ 83 ], consistent with our results at both 5 and 10 dyn.cm. −2 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…RhoA inhibition was already reported in bovine primary BMEC cultured one day at 10 dyn.cm −2 [ 80 ]. More recently, DeOro et al reported in a pre-print an inhibition of RhoA in hCMEC/D3 cells (4 days at 2.1 dyn.cm −2 ) [ 83 ], consistent with our results at both 5 and 10 dyn.cm. −2 .…”
Section: Resultssupporting
confidence: 93%
“…Brown et al showed that ZO-1 and Claudin-5 intensities at the cell membrane were increased after 2.73 dyn.cm −2 exposure for 18 h in a parallel-plate flow dual chamber [ 45 ]. DeOre et al confirmed the increase in ZO-1 expression by immunofluorescence [ 83 ]. They cultivated hCMEC/D3 cells with astrocytes in artificial capillaries with SS from 0.18 to 2.1 dyn.cm −2 for 4 days.…”
Section: Resultsmentioning
confidence: 95%
“…In the absence of interstitial flow, we observe that ECM HA inhibits endothelial sprouting. This result is consistent with previous reports that under in vitro static conditions, addition of HA to collagen ECM inhibits capillary tube formation [37] and enhances vascular barrier function [35] . Indeed, we previously reported that the addition of HA to collagen-based matrices suppresses both vessel sprouting and permeability under static in vitro conditions and in the absence of CXCL12 treatment [21] .…”
Section: Discussionsupporting
confidence: 94%
“…This outcome is surprising because the CD44 receptor is known to be mechanosensitive. For example, a recent study showed that CD44 strengthens monoculture brain endothelial cell barrier function in the presence of intravascular fluid shear stress in vitro [35] . Moreover, multiple studies have reported that interstitial flow promotes cancer cell invasion via CD44-mediated mechanisms [36] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, CD44 regulates adhesion through Rac1 activation. 67,88 The metastatic foci, in general, have enhanced glycolytic capacity. 89 This reflects the underlying cellular signaling context of metastatic cells.…”
Section: Reversible Hybrid-emt the Slow-and-steady Pathway For Metast...mentioning
confidence: 99%